Kinetics and mechanisms of electrochemical reactions on platinum with solutions of iodine-sodium iodide in acetonitrile - Macagno, V. A. (1969)
The kinetics of the iodine-tri-iodide-iodide electrode in acetonitrile has been investigated in the temperature range from 0 to 30°C. Current/voltage curves were determined using a platinum rotating disk electrode working at 200 to 3000 rpm. The anodic and cathodic current/voltage curves are characterized by two well defined waves. The total reactions related to the first and second anodic waves are respectively 3I− = I3− + 2 e and 2I3− = 3I2 + 2 e, while the reverse reactions represent the second and first cathodic waves respectively. The diffusion coefficients of the diffusing species have been evaluated. Current/voltage curves in the region preceding the limiting cd exhibit a measurable irreversibility. The kinetic parameters related to the activated process were determined, and the kinetics of the reactions interpreted in terms of reaction mechanisms that involve an ion plus atom reaction as rate determining step for the anodic process and the reverse reaction for the cathodic process.